O možnosti ekokritiškega pogleda na tematizacijo "ne-človeške subjektivnosti" v literaturi - Kernev-Štrajn, Jelka (Primerjalna književnost, 2007)
This article calls into question the thematization of animals in literature and advances the thesis that a closer examination of the representation of nonhuman subjectivity provides a productive starting point for a critique of the anthropocentric attitude in literature and in literary interpretation as well. The article therefore enters the field of ecocriticism, which - as one of the latest trends in literary criticism - deals with the interconnections between nature and culture. On the one hand, this reflection is grounded in the Kantian concept of the sublime, which implies the notion of unrepresentability. On the other hand, it relies on two other epistemological tools, these being "anomaly" and "becoming animal", taken from Mille plateaux (Deleuze and Guattari).
Keywords: svetovna književnost; živali; literarna estetika; literarna interpretacija; antropocentrizem; sublimno